Reed- Phragmitis Karka based constructed wetland for the treatment of domestic wastewater in Ujjain city of central India - Panwar, R.S.; Makvana, K.S. (International Journal of Scientific Research in Biological Sciences, 2017)
Constructed wetland with horizontal subsurface flow have been used wastewater treatment in India more than 35 years. Water scarcity is likely to become more geometrical proposition in the near future due to rapid population growth, increasing per capita water consumption and geographical disparities or inequalities between centers of population growth and availability of water CWS after an effective mean of integrating wastewater treatment and resources enhancement, often at competitive cost in comparison to conventional wastewater treatments, with additional benefit of green urban landscaping and wildlife habitat. In present research work various pollutants have been removed from domestic wastewater like TS, TSS, TDS, DO, TKN, NH4+-N, COD and BOD by 78%, 80%, 76.48%, 135.41%, 69.53%, 69%, 78.64% and 69.54%. The constructed wetland system is located in upstream of wastewater nullah on MR-II road site in Mahankal Commercial Area at Ujjain city with (23°12`N latitude, 75°42`E longitude) mean sea level 515.45 m in the central part of India. Phragmites Karka the tropical emergent grass over 60 cm depth peanut size gravel bed planted. The system specially designed for domestic wastewater treatment. The treatment system covered effective surface area of 900 m2 (length 100m x width 9m), retention capacity 75m3/day. Phragmites Karka the indigenous tropical emergent grass cosmopolitan species found in north America, Mexico, Great britain, Euresia, India, Africa, Newzealand and Australia. In India species is a distributed widely in the north and indo Gangetic plain of humid area. Phragmites Karka (Reed Grass) play important role in removing pollutant when strategically planted in eco engineered system.